Reconciliation, resilience and resistance in Inuit teacher's professional development and practices - Kathy Snow; Shelley Tulloch; Heather Ochalski; Melanie O'Gorman (Education in the North, 2018)
In February 2017, 26 Inuit educators gathered in Nain, Nunatsiavut for the Inuit Education Forum. Teachers from each of the four Inuit regions in Canada were invited to share their experiences on education in Inuit Nunangat with the goal of identifying barriers and promising practices occurring within their communities. One of the key themes arising from these conversations was the ongoing need for Inuit teacher support and development in schools. Training and retaining Inuit teachers is problematic in Canada, while research tells us that both of these factors are key to student success. Some key challenges impacting resilience for teachers identified by the Inuit Education Forum participants were: organization of learning and leadership, prioritization of Inuit language and culture in schools, and negotiations of teachers’ isolation and autonomy. These challenges and the solutions offered by participants are discussed in the Canadian historical context implications for teacher training and professional development in Inuit Nunangat are highlighted.